THE APPLICATION OF HIDRAM PUMPS AS APPROPRIATE TECHNOLOGY FOR THE KADUBEREUM VILLAGE FARMERS GROUP – PADARINCANG - Rahmatullah, Asep; Hidayatullah, Ikhsan Maulana; Mahmudi, Udi; Maulana, Akhmad Rifqi (Nindikayla Institute, 2024)
Kadubeureum Village is one of the villages located in Padarincang, Serang Regency, Banten Province. Kadubeureum village has 976,235 ha with a rice field area of 362,432 ha or about 37.16% of the existing area. So, this area is one of the agricultural sector areas in Padarincang Subdistrict. Irrigation in the rice fields in Kadubeurem Village is divided into 2 types of irrigation: rice fields that use irrigation from irrigation sourced from springs and rivers, and rice fields that still rely on rain (rice fields that have rain). This rain-fed rice field area is caused by rice fields above the river stream and are not watered from irrigation. So that the level of harvest productivity in the rain-affected rice fields is relatively lower than the area of rice fields that are irrigated. This becomes a problem for farmers whose rice fields include rice fields that have rain due to the location of the rice fields that are above the river flow. Seeing the above, it is necessary to apply appropriate technology for innovative in overcoming problems in farmers groups with the application of appropriate technology, namely with the application of hydrant pumps that are economical, efficient and effective so that the problem of water shortage in rice fields can be resolved.